Radiotherapy versus transoral robotic surgery and neck dissection for oropharyngeal squamous cell carcinoma (ORATOR): an open-label, phase 2, randomised trial. Issue 10 (October 2019) - Nichols, Anthony C; Theurer, Julie; Prisman, Eitan; Read, Nancy; Berthelet, Eric; Tran, Eric; Fung, Kevin; de Almeida, John R; Bayley, Andrew; Goldstein, David P; Hier, Michael; Sultanem, Khalil; et al.
Summary: Background: Transoral robotic surgery (TORS) with concurrent neck dissection has supplanted radiotherapy in the USA as the most common treatment for oropharyngeal squamous cell carcinoma (OPSCC), yet no randomised trials have compared these modalities. We aimed to evaluate differences in quality of life (QOL) 1 year after treatment. Methods: The ORATOR trial was an investigator-initiated, multicentre, international, open-label, parallel-group, phase 2, randomised study. Patients were enrolled at six hospitals in Canada and Australia. We randomly assigned (1:1) patients aged 18 years or older, with Eastern Cooperative Oncology Group scores of 0–2, and with T1–T2, N0–2 (≤4 cm) OPSCC tumour types to radiotherapy (70 Gy, with chemotherapy if N1–2) or TORS plus neck dissection (with or without adjuvant chemoradiotherapy, based on pathology). Following stratification by p16 status, patients were randomly assigned using a computer-generated randomisation list with permuted blocks of four. The primary endpoint was swallowing-related QOL at 1 year as established using the MD Anderson Dysphagia Inventory (MDADI) score, powered to detect a 10-point improvement (a clinically meaningful change) in the TORS plus neck dissection group. All analyses were done by intention to treat. This study is registered with ClinicalTrials.gov (NCT01590355 ) and is active, but not currently recruiting. Findings: 68 patients were randomly assigned (34 per group) between Aug 10, 2012, and June 9, 2017. Median follow-up was 25 months (IQR 20–33) for the radiotherapy group and 29 months (23–43) for the TORS plus neck dissection group. MDADI total scores at 1 year were mean 86·9 (SD 11·4) in the radiotherapy group versus 80·1 (13·0) in the TORS plus neck dissection group (p=0·042). There were more cases of neutropenia (six [18%] of 34 patients vs none of 34), hearing loss (13 [38%] vs five [15%]), and tinnitus (12 [35%] vs two [6%]) reported in the radiotherapy group than in the TORS plus neck dissection group, and more cases of trismus in the TORS plus neck dissection group (nine [26%] vs one [3%]). The most common adverse events in the radiotherapy group were dysphagia (n=6), hearing loss (n=6), and mucositis (n=4), all grade 3, and in the TORS plus neck dissection group, dysphagia (n=9, all grade 3) and there was one death caused by bleeding after TORS. Interpretation: Patients treated with radiotherapy showed superior swallowing-related QOL scores 1 year after treatment, although the difference did not represent a clinically meaningful change. Toxicity patterns differed between the groups. Patients with OPSCC should be informed about both treatment options. Funding: Canadian Cancer Society Research Institute Grant (#701842 ), Ontario Institute for Cancer Research Clinician-Scientist research grant, and the Wolfe Surgical Research Professorship in the Biology of Head and Neck Cancers grant.